How will 1992 affect the rest of the world? The reactions of some major countries and trade blocs towards EC integration - Amy Skolnik (Bank of Finland, 1988)
Given the interdependence of today's global markets, it would be impossible for European integration to occur without affecting the rest of the world. The current triangle between the U.S., Japan, and EC is very precarious and none of these countries can avoid the others' influences. However, this is a matter that the EC seems to be neglecting and with the coming of 1992, many countries fear that the internal market will result in a rise in trade barriers and protectionism for everyone outside. This paper looks at the reactions and concerns of the U.S. and Japan towards the internal market as well as EC relations with Eastern European and EFTA countries. Though the true affects of 1992 are impossible to predict, and the EC Commission claims that no "European fortress" is being built, many of its actions indicate otherwise. In response, much of the rest of the world is discussing alternative methods and the possibility of new trade associations. With this international cooperation in mind, it is not in the EC's best interest to alienate itself from the rest of the world's markets.
URN:NBN:fi:bof-201908051333
Keywords: 330